Design and synthesis of novel 2, 4-diaryl-5H-indeno[1, 2-b]pyridine derivatives, and their evaluation of topoisomerase inhibitory activity and cytotoxicity. Issue 1 (1st January 2015) - Kadayat, Tara Man; Park, Chanmi; Jun, Kyu-Yeon; Magar, Til Bahadur Thapa; Bist, Ganesh; Yoo, Han Young; Kwon, Youngjoo; Lee, Eung-Seok
Graphical abstract